Transforming Education for a Sustainable Future: A Religious Ethical Perspective - Muhammad, Adamu Abubakar; Dalhatu, Rabi Shehu; Ardo, Adam Muhammad; Shariff, Ikilima Abubakar; Muhammad, Yakubu Zulaihat (Perwakilan: Journal of Good Governance, Diplomacy, Customary Institutionalization and Social Networks, 2025)
Everyone agrees that education is essential to both personal advancement and society change. The objective of sustainable development is threatened in the twenty-first century by a number of interrelated issues that the world community must deal with, including inequality, ecological degradation, moral decay, and technological disruption. In order to create a sustainable future, this paper investigates how religion, as a source of ethical and spiritual knowledge, might revolutionize education. The study combines UNESCO's Education for Sustainable Development (ESD) goal with religious ethical frameworks using a qualitative and conceptual methodology. The results show that the moral underpinnings required to shift education towards sustainability are provided by faith-based values, such as stewardship, justice, compassion, and the pursuit of knowledge. The study focusses on case studies from indigenous, Christian, and Islamic traditions that effectively connect religious principles with social and environmental responsibility. In order to achieve the aims of global sustainability, it calls for greater cooperation between governments, faith-based organizations, and educators. It concludes that a spiritually orientated education fosters societal harmony and comprehensive human development.